The Effect Of Naupli Artemia Feeding Which Is Enriched By Squal ene In Different Dose On The Growth And Survival Rate Or Larval Perch (Lates calcarifer) - Pridona, Rahma; Tang, Usman M; ', Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A feeding experiment was conducted to determine the optimal dose of growth and survival rate for larval perch (Lates calcarifer). Larval initial average weight 0,022 g, initial average body length 7,38 mm and old 15 days. Completely randomized design with five treachments and three replications were use : A (naupli artemia), B (naupli artemia + squalene 0,3 g/L), C (naupli artemia + squalene 0,6 g/L), D (naupli artemia + squalene 0,9 g/L), E (naupli artemia + squalene 1,2 g/L). The results showed that the growth in survival rate, growth of body weight (AW), and growth of body length(AL). Based on the evaluation of the some parameters ; SR (80,6%), AW(0,813 g) AL (3,21 cm)and SGR (16,1 % day). It can be concluded that treatment D (naupli + squalene 0,9 g/L) is optimal for growth and survival rate for larval perch (Lates calcarifer).Key words : Lates calcarifer, different dose, enriched by squalene